The Effect of Providing Low Purine Diet Education with Booklet Media on Knowledge and Purine Intake in Gouty Arthritis Sufferers in the Pasundan Community Health Center Working Area - Singgih Dwi Karsono; Kurniati Dwi Utami; Mustaming; Joko Sapto Pramono (Formosa Journal of Science and Technology, 2023)
Gouty arthritis is a common disease throughout the world and its prevalence has increased in the last 50 years. Based on the fourth quarter report at the Pasundan Community Health Center, there were 113 cases of gout arthritis. Diet is a factor that causes an increase in uric acid in the blood. So it is important to provide education with booklets to regulate diet management for gouty arthritis. This study aims to determine the effect of low-purine diet education with booklets on knowledge and purine intake in gouty arthritis sufferers. Pre-Experimental Research Design via One Group Pretest-Posttest Design involving 26 gout arthritis sufferers in the Pasundan Community Health Center working area, sampling using a purposive sampling technique. Data were analyzed using the paired sample t-test. The results obtained increased knowledge (p-value = 0.000) and changes in purine intake (p-value = 0.000).